Alpha-Amylase and Glucoamylase Inhibitory Assessment of Methanol Extract of Fagonia Indica and its GC-MS analysis - Atiq-ur-Rehman; Sana ullah Umair; Fatima Aslam (Iraqi Journal of Pharmaceutical Sciences, 2024)
The aim of the present study was to investigate the inhibition of enzymes alpha-amylase and glucoamylase by methanol extract of the plant Fagonia indica Burm.f. responsible for hypoglycemic activity. This study was performed for phytochemical investigation of this plant using the standard methods. Both qualitative and quantitative analysis of methanol extract of the plant was done for the analysis and estimation of phytochemical constituents. Alpha-amylase and glucoamylase inhibition by this extract was assessed for the evaluation of hypoglycemic activity. Gas chromatographic-mass spectrometric (GC-MS) analysis of hypoglycemic methanol extract was done to identify the compounds responsible for this activity. Phytochemical analysis exhibited the presence of various phytoconstituents in methanol extract. The maximum %age of enzymes inhibition of this extract was 49.1 ± 2.4% (IC50 values of 104.2 ± 8.7 μg/ml) and 31.7 ± 2.9% (IC50 values of 273.7 ± 54.6 μg/ml) for alpha amylase and glucoamylase enzymes respectively at 100 μg/ml concentration. The standard acarbose showed 68.91±3.0% (IC50=52.9±4.8 μg/ml) and 57.3±0.4% (IC50=70.2±3.4 μg/ml) inhibition of these enzymes respectively at the same concentration. GC-MS analysis identified 15 compounds in this extract. This finding confirms traditional use of this plant in managing diabetes.